Implementation Of An E-Learning Media Management Strategy In The Improvement Of The Learning Performance Of Mathematics In Private Universities - Lia Saniah; Melinda Putri Mubarika; Wati Irnawati (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2024)
This study aims to examine instructors' e-learning management strategies to improve student learning. This qualitative research uses descriptive methods and involves lecturers who have experience in online learning and have been successful in improving learning outcomes through e-learning. The focus of the study is on the strategies used by the instructors in the planning, implementation, monitoring, and evaluation of online learning (e-learning). The research instrument employs interview guidelines and documentation. The data collection technique used in this study is an interview with an increased focus on the presentation of e-learning on the website and the documentation of the website. Data analysis is conducted using data triangulation techniques. The findings indicate that the e-learning management strategy of the instructor includes planning by creating a learning plan on the e-learning website that includes a subset of RPS (lesson plan), learning outcomes, diagnostic test (pre-test), module materials, learning videos, journal links related to materials, discussion forums, assignments, and absorption test (post-test). Supervision of e-learning is conducted through agreed e-learning time, monitoring via Zoom, video conference, and WhatsApp group to assess student engagement. Evaluation is done through diagnostic and absorption tests to gauge student understanding and improve higher-order thinking skills (HOTS). The website's e-learning content is evaluated using the CIPP (Context, Input, Process, and Output) model to promote continuous innovation from lecturers